Chromatographic spot test for aluminum determination in soils, using 1,2, dihydroxyantraquinone as reagent - Fernandes, Clóvis Silva (Pesquisa Agropecuaria Brasileira, 2014)
A new chromatographic spot test for detection and approximative evaluation of aluminum toxicity in soil is described. The test was processed by means of percolation of a NaCl 1 N soil extract, through a "confined" spot test paper impregnated with a 1,2.dihydroxyantraquinone derivative. In the presence of Al3+ displaced from the soil, in the extract, a red lake band of 1,2.dihydroxyantraquinone-aluminum complex took place. The red band length is directly related to the Al3+ concentration. Both analysis of Al3+ versus band length and its mathematical expression are also presented. The test can be useful for rapid prospection in the research of pedology, phytopathology, ecophysiology and plant science.